A Retrospective Comparative Study of Different Methods of Blood Management in Total Knee Replacement - Pappa, Eleni; Vergados, Nikolaos; Spiridakis, Emanouil; Chountas, George; Apostolopoulou, Anna; Sourmelis, Savas (The Journal of Knee Surgery, 2019)
Perioperative blood management is essential to minimize allogeneic blood transfusion in total knee replacement. The effect of preoperative administration of erythropoietin, intraoperative cell saver, tranexamic acid, and restrictive transfusion strategies on allogeneic transfusion is studied in total knee replacement. A retrospective comparative study of 106 patients who underwent total knee replacement in different time periods was performed. Group A (n1 = 45) underwent restrictive strategies of transfusion between 2009 and 2010. Group B (n2 = 24) includes patients where erythropoietin of either 10.000 IU or 20.000 IU was given preoperatively. Patients of Group C (n3 = 21) underwent autologous washed erythrocytes transfusion through a cell saver. Lastly, in Group D (n4 = 15) tranexamic acid dose of 1 gr IV was given intraoperatively. The preoperative and discharge hemoglobin together with total units of blood transfusion and creatinine levels was studied. Tranexamic acid noted the least units of blood transfusion (mean = 0.82 units/patient, p < 0.001, CI 95%) in contrast to the two regimens of erythropoietin (1.16 units/patient) OrthoPAT (1.43 units/patient) and restrictive strategies (1.92 units/patient). The mean preoperative hemoglobin was 13.37 g/dL with no statistical difference among the groups of patients. The postoperative mean hemoglobin was 10.59 with no statistical difference among the groups of patients too. Additionally, the mean creatinine level was 0.93 mg/dL; however, no statistical difference among the groups of patients was noted. Finally, tranexamic acid seemed to be the most cost-effective regime. In our study, tranexamic acid proved its superiority concerning the postoperative blood transfusion on patients undergoing total knee replacement, in comparison with the other existing methods of perioperative blood management. This is a Level III, retrospective comparative study.
Keywords: blood management; total knee replacement; tranexamic acid